Community initiative: community-based participatory research in a region of Mexico - Arenas Monreal, Ma de la Luz; Pacheco Magaña, Lilian Erendira; Espinosa Cardenas, Frida; Cortez Lugo, Marlene; Rueda Neria, Celina; Valdez Santiago, Rosario (Horizonte Sanitario, 2024)
Objectives: To characterize a community initiative based on the principles of Community Based Participatory Research carried out with the population of a rural community in Mexico. Methods: The community initiative employed mixed methods. A participatory health diagnosis was conducted, identifying two primary issues: environmental concerns and a lack of alternatives for children and adolescents. A collaborative group was established comprising community members, researchers, and local authorities. This group was subdivided into two teams to address each identified issue. Workshops were organized and financial support was secured. Results: Both groups successfully secured funding. One subgroup formed a traditional music band, which, along with the families of participating children and adolescents, organized a series of cultural activities that bolstered the community both individually and collectively. The other group focused on urban solid waste, receiving training from local community organizations. They conducted awareness workshops on waste separation, recycling, reduction, and composting within the community, and established a collection center at a local school. Their efforts expanded to include the installation of biodigesters and cleaning of the community’s streams and ravines. Conclusions: Public health initiatives are enhanced when rooted in approaches like Community Based Participatory Research, yielding improved outcomes for the population and enhanced learning for research teams. Keywords: Community-Based Participatory Research; Rural Population; Mexico; Social Vulnerability.